2022
DOI: 10.21203/rs.3.rs-1702574/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comprehensive single-cell atlas of freshly-dissociated human synovium in inflammatory arthritis with an optimized dissociation protocol for prospective fresh synovial biopsy collection

Abstract: Single-cell RNA-sequencing is advancing our understanding of synovial pathobiology in inflammatory arthritis. Here, we optimized the protocol for dissociation of synovial biopsies and created a comprehensive reference single-cell atlas of fresh human synovium in inflammatory arthritis. We derived our protocol from the published dissociation method for cryopreserved synovium (Donlin L. et al. Arthritis Res. Ther. 2019) with modifications to enrich synovial cells and minimize cell loss. These modifications enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Regarding cells participating in the pathogenesis of synovitis, altered endothelial cell (EC) function and angiogenesis have been proven to play an important role. Edalat et al 12 created a comprehensive single-cell atlas of synovial ECs in patients with inflammatory arthritis, which provides a reference data set for future EC subtype-specific functional studies. As for inflammatory cells, by applying single-cell RNA sequencing together with B and T cell repertoire sequencing in synovial tissue and matched peripheral blood, Meednu et al 13 revealed tissue-specific clonal expansion and in situ selection of B and T cells in the synovium of RA patients.…”
Section: Single-cell Sequencing Revealed the Underlying Pathogenesis ...mentioning
confidence: 99%
“…Regarding cells participating in the pathogenesis of synovitis, altered endothelial cell (EC) function and angiogenesis have been proven to play an important role. Edalat et al 12 created a comprehensive single-cell atlas of synovial ECs in patients with inflammatory arthritis, which provides a reference data set for future EC subtype-specific functional studies. As for inflammatory cells, by applying single-cell RNA sequencing together with B and T cell repertoire sequencing in synovial tissue and matched peripheral blood, Meednu et al 13 revealed tissue-specific clonal expansion and in situ selection of B and T cells in the synovium of RA patients.…”
Section: Single-cell Sequencing Revealed the Underlying Pathogenesis ...mentioning
confidence: 99%